Analysis of semi buried cylindrical water tank by finite element method and classical approach - ferdinand, Niyonyungu; callixte, Niyonsaba (International Journal of Engineering and Technology, 2019)
Classical approach is mostly where the access to finite element software is expensive, but it is limited to some structures with non-uniformity and it is time consuming. This paper explains the results from classical and finite element analysis of water tank by considering fixed base and free base loading condition. Thereafter, there are the comparison of the results (hoop stresses) obtained from finite element method with those obtained from classical approach. The comparison shows that the good results of finite element analysis are obtained when the tank is meshed into more elements.Â Â